2012
DOI: 10.1371/journal.pone.0045185
|View full text |Cite
|
Sign up to set email alerts
|

CD80 and CD86 Differentially Regulate Mechanical Interactions of T-Cells with Antigen-Presenting Dendritic Cells and B-Cells

Abstract: Functional T-cell responses are initiated by physical interactions between T-cells and antigen-presenting cells (APCs), including dendritic cells (DCs) and B-cells. T-cells are activated more effectively by DCs than by B-cells, but little is known about the key molecular mechanisms that underpin the particular potency of DC in triggering T-cell responses. To better understand the influence of physical intercellular interactions on APC efficacy in activating T-cells, we used single cell force spectroscopy to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 59 publications
3
80
0
3
Order By: Relevance
“…Our data show that after immunization with soluble antigen and double-stranded RNA, Xcr1-expressing migratory DCs that have newly arrived in the SDLN interacted with antigen-specific CD8 + T cells more prominently than other Xcr1-expressing DCs, i.e., LN-resident DCs and the migratory DCs that had arrived in the LNs before immunization. Future studies need to test whether the superior interaction ability is dependent on the prominent upregulation of CD86 and CD80 by the newly arriving migratory DCs, because the costimulatory molecules can strengthen antigendependent interactions between T cells and DCs (27). It is also likely, but not certain, that the newly arriving migratory DCs present the highest amounts of peptides after they have encountered antigen plus double-stranded RNA in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that after immunization with soluble antigen and double-stranded RNA, Xcr1-expressing migratory DCs that have newly arrived in the SDLN interacted with antigen-specific CD8 + T cells more prominently than other Xcr1-expressing DCs, i.e., LN-resident DCs and the migratory DCs that had arrived in the LNs before immunization. Future studies need to test whether the superior interaction ability is dependent on the prominent upregulation of CD86 and CD80 by the newly arriving migratory DCs, because the costimulatory molecules can strengthen antigendependent interactions between T cells and DCs (27). It is also likely, but not certain, that the newly arriving migratory DCs present the highest amounts of peptides after they have encountered antigen plus double-stranded RNA in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences (Table II) were designed according to GenBank and synthesized by DaAn Gene Co., Ltd. of Sun Yat-Sen University (Guangzhou, China). At 24 h post-transfection, the total RNA of 1x10 6 DCs was extracted using TRIzol reagent (Invitrogen; Thermo Fisher Scientific, Inc.) and reverse transcribed and amplified using QuantiTect SYBR Green RT-PCR kit (Qiagen GmbH, Hilden, Germany) in a Roche LightCycler 480 (Roche Diagnostics, Basel, Switzerland). The amplifications were carried out according to the manufacturer's protocol for the QuantiTect SYBR Green RT-PCR kit (Takala, Japan).…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Activation of T cells requires signals which are initiated via the TCR complex and cluster of differentiation (CD) 28. Mature dendritic cells (mDCs) express high levels of the co-stimulatory molecules CD80 and CD86, which provide the signal that is required for triggering T cell activation, expansion and differentiation via interaction with CD28 (6). Previous studies have demonstrated that CD80 and CD86 levels are elevated in patients with asthma (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the expression of distinct molecules associated with B cell activation was evaluated in CD27+IgM+B cells. CD86 is a critical co-stimulatory molecule to facilitate the interaction of T cells with B cells (30). CD95 is a death receptor, which initiates extrinsic pathways of apoptosis to remove activated immune cells (31).…”
Section: Discussionmentioning
confidence: 99%
“…To measure the phenotypic features of peripheral IgM+B cell subsets, 1x10 6 PBMCs were incubated in 200 µl blocking solution consisting of 2% bovine serum albumin (Genview Corp., Houston, TX, USA) in PBS for 30 Following washing twice with PBS, the cells were fixed with 1% paraformaldehyde in the dark at 4˚C for 12 h. Then the expression of surface molecules on cells were assayed using the BD FACSCalibur (BD Biosciences) and data were analyzed using FlowJo 7.6 software (Tree Star, Inc., Ashland, OR, USA). Based on expression of CD5, B cells were divided into CD5+B cells (B1 cells) and CD5-B cells (B2 cells) (20).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%